1972
DOI: 10.1042/bj1260361
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties and subunit structure of l-asparaginase isolated from Erwinia carotovora

Abstract: 1. l-Asparaginases from Erwinia carotovora and Escherichia coli (EC2 enzyme) are both capable of inhibiting and eliminating certain types of tumour cells. The Er. carotovora enzyme is a more basic protein, however, and in contrast with the EC2 enzyme it contains neither tryptophan nor cystine, and disulphide bonds are therefore absent. The molecule is very stable in solution from pH3.0 to about pH12.0, and is somewhat more stable at alkaline pH than is the Esch. coli enzyme. Calculations based on a s(0) (20,w)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0
5

Year Published

1973
1973
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 48 publications
4
31
0
5
Order By: Relevance
“…We think that the most adequate solution is to measure Erwinia asparaginase concentrations by the Biuret or modified Lowry [18] methods, where the aromatic-residue content is not significant. We used the latter method in our study and the activity of recombinant asparaginase (630 i.u./mg) corresponded well with that of the wild-type enzyme (550 i.u./ mg) when protein concentration had been determined with amino acid Technicon AutoAnalyser [25].…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…We think that the most adequate solution is to measure Erwinia asparaginase concentrations by the Biuret or modified Lowry [18] methods, where the aromatic-residue content is not significant. We used the latter method in our study and the activity of recombinant asparaginase (630 i.u./mg) corresponded well with that of the wild-type enzyme (550 i.u./ mg) when protein concentration had been determined with amino acid Technicon AutoAnalyser [25].…”
Section: Resultsmentioning
confidence: 85%
“…The reported activities of wild-type L-asparaginase from Erw. carotovora vary from 310 [21] to 550 i.u./mg [25]. For ErA activities this range is even larger, namely from 200 [27] to 615 i.u./mg [22].…”
Section: Resultsmentioning
confidence: 99%
“…carotovora [61][62][63][64][65][66], P. vulgaris [67], V. succinogenes [26], S. marcencens [68] Для получения бесклеточного экстракта на первом этапе очистки клетки разрушают ультразвуком. Полученный после ультрацентрифугирования (30000 g) супернатант последовательно подвергается хроматографии на колонках с Q-Sepharose и DEAE-Toyopearl 650m (L-аспарагиназы RrA и YpA) [52,53] или SP-Sepharose (L-аспарагиназа Нра) [54].…”
Section: выделение и очистка рекомбинантных L-аспарагиназunclassified
“…Действительно, некоторые L-аспарагиназы характеризуются значительной структурной устойчивостью в денатурирующих условиях, которая может показаться удивительной для фермента с нековалентно связанными субъединицами. Например, после 48-часовой инкубации в 0,2 М фосфатном буфере, (рН 7,4), содержащем 8 М мочевину, диссоциируют только 50% молекул ErA [61]. Интересно отметить, что олигомеризация L-аспарагиназы является субстрат-зависимым процессом, что предполагает возможность аллостерической регуляции каталитической активности.…”
Section: энзимологическая характеристика новых рекомбинантных бактериunclassified
“…Using DONV with absorbance at 274 nm as an alternative substrate, and also using a double-sector cell that allowed layering of enzyme into both sectors at once, thus canceling enzyme absorbance, Holcenberg et al (79) determined the specific activities of various portions of the sedimentation velocity profile. They found that the slower-sedimenting species had less than 4% of the activity of the tetramer, Cammack et al (39) also report that the subunits in Erwinia asparaginase are inactive. In fact, there is no evidence so far to suggest that the subunits of any asparaginase have activity.…”
Section: B Molecular Weight Shape and Subunitsmentioning
confidence: 99%